IKHTIAR HIMPUNAN MAHASISWA ISLAM CABANG JAMBIDALAM MEMBENTUK BUDAYA MEMBACA DI KALANGAN MAHASISWA SERTA AKTIVIS - Harahap, Pandu Wijaya Nagari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
ABSTRACK This writing aims to determine the pattern and culture of reading among HMI Jambi Branch organizations and to complete the requirements as a candidate for General Chair of the Jambi Branch of HMI. positive encouragement to respond to the dynamics of the times both now and in the future. One of the weapons prepared to respond to the upheavals of the times is to foster a reading culture among activists. Efforts that must be made to create a reading culture include the establishment of discussion forums, scientific studies, book reviews and other activities that can provide stimulus to HMI cadres to create a reading culture. The reading culture is an effort to contextualize the objectives of HMI contained in article 4 of the Articles of Association